2016
DOI: 10.1002/adhm.201600318
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Polymer‐Based, Fully Organic Prosthesis for Implantation into the Subretinal Space of the Rat

Abstract: Replacement strategies arise as promising approaches in case of inherited retinal dystrophies leading to blindness. A fully organic retinal prosthesis made of conjugated polymers layered onto a silk fibroin substrate is engineered. First, the biophysical and surface properties are characterized; then, the long-term biocompatibility is assessed after implantation of the organic device in the subretinal space of 3-months-old rats for a period of five months. The results indicate a good stability of the subretina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(74 citation statements)
references
References 59 publications
(25 reference statements)
2
72
0
Order By: Relevance
“…5,33,34 We initially considered that photoelectric dye-coupled polyethylene films in subretinal space of RCS rats' eyes would exert a similar protective effect on the retina, as described for other materials. This study revealed that the photoelectric dye could slow down the process of retinal degeneration in RCS rats.…”
Section: Discussionmentioning
confidence: 99%
“…5,33,34 We initially considered that photoelectric dye-coupled polyethylene films in subretinal space of RCS rats' eyes would exert a similar protective effect on the retina, as described for other materials. This study revealed that the photoelectric dye could slow down the process of retinal degeneration in RCS rats.…”
Section: Discussionmentioning
confidence: 99%
“…d,e) (d) GFAP and (e) FGF expression of a sham‐operated retina and a retina with an implanted device. Reproduced with permission . Copyright 2016, WILEY‐VCH.…”
Section: Bioinspired Visual Prosthesesmentioning
confidence: 99%
“…Photovoltaic retinal prostheses that use soft organic materials have been developed as a solution (Figure c) . Such photovoltaic prostheses consist of a fibroin silk substrate, a poly(3‐hexylthiophene) (P3HT) photoabsorbing layer, and a PEDOT:polystyrene charge transfer layer.…”
Section: Bioinspired Visual Prosthesesmentioning
confidence: 99%
“…Ex vivo studies of the direct optical stimulation of explanted blind retina by the conjugated polymer poly(3‐hexyl thiophene) (P3HT) based devices have shown neuronal responses similar to those of healthy retina . A photovoltaic implant composed of P3HT, PEDOT:PSS and silk fibroin was implanted subretinally in rats for 5 months and showed excellent biocompatibility, relative retention of the optoelectronic layer, and good contact with the internal retina . The same device was then implanted for 6 to 10 months in Royal College of Surgeons (RCS) rats commonly used as a model for retinitis pigmentosa.…”
Section: Conjugated Polymers Tested In Vivomentioning
confidence: 99%